Surfactant Protein A, a Novel Regulator for Smooth Muscle Phenotypic Modulation and Vascular Remodeling—Brief Report. Issue 2 (February 2021) - Ran, Ran; Cai, Dunpeng; King, Skylar D.; Que, Xingyi; Bath, Jonathan M.; Chen, Shi-You
Abstract : Objective: The objective of this study is to determine the role of SPA (surfactant protein A) in vascular smooth muscle cell (SMC) phenotypic modulation and vascular remodeling. Approach and Results: PDGF-BB (Platelet-derived growth factor-BB) and serum induced SPA expression while downregulating SMC marker gene expression in SMCs. SPA deficiency increased the contractile protein expression. Mechanistically, SPA deficiency enhanced the expression of myocardin and TGF (transforming growth factor)-β, the key regulators for contractile SMC phenotype. In vivo, SPA was induced in medial and neointimal SMCs following mechanical injury in both rat and mouse carotid arteries. SPA knockout in mice dramatically attenuated the wire injury-induced intimal hyperplasia while restoring SMC contractile protein expression in medial SMCs. These data indicate that SPA plays an important role in SMC phenotype modulation and vascular remodeling in vivo. Conclusions: SPA is a novel protein factor modulating SMC phenotype. Blocking the abnormal elevation of SPA may be a potential strategy to inhibit the development of proliferative vascular diseases. Abstract : Supplemental Digital Content is available in the text.